2015
DOI: 10.1021/acsnano.5b01631
|View full text |Cite
|
Sign up to set email alerts
|

Orientational Control of Colloidal 2D-Layered Transition Metal Dichalcogenide Nanodiscs via Unusual Electrokinetic Response

Abstract: We report an unusual response of colloidal layered transition metal dichalcogenide (TMDC) nanodiscs to the electric field, where the orientational order is created transiently only during the time-varying period of the electric field while no orientational order is created by the DC field. This result is in stark contrast to the typical electrokinetic response of various other colloidal nanoparticles, where the permanent dipole or (and) anisotropic-induced dipole creates a sustaining orientational order under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Note, while a dipole is a vector in three dimensions, characterized by two angles: θ and φ , we only track the angle α between the projection of the dipole onto the horizontal plane and a fixed axis in this plane (see Methods). On a qualitative level, the presence of a permanent dipole is immediately visible 39 : switching the field polarity makes the particle orientation flip ( Video 2 in the Supplementary Material ); no such flipping of particle orientation is possible for an isotropic sphere with an induced dipole 2 . To make a more systematic measurement, we follow the Brownian fluctuations of α , with the particle subject to a fixed E 0 .…”
Section: Resultsmentioning
confidence: 99%
“…Note, while a dipole is a vector in three dimensions, characterized by two angles: θ and φ , we only track the angle α between the projection of the dipole onto the horizontal plane and a fixed axis in this plane (see Methods). On a qualitative level, the presence of a permanent dipole is immediately visible 39 : switching the field polarity makes the particle orientation flip ( Video 2 in the Supplementary Material ); no such flipping of particle orientation is possible for an isotropic sphere with an induced dipole 2 . To make a more systematic measurement, we follow the Brownian fluctuations of α , with the particle subject to a fixed E 0 .…”
Section: Resultsmentioning
confidence: 99%
“…Mechanical alignment is an old and general method that can be applied to almost every nanomaterial, but the control by a magnetic or electrical field offers more flexibility and is more suitable for device applications. Magnetic or electrical field alignment of most nanomaterials such as CNT, graphene oxide flakes, or 2D transition metal dichalcogenides has been achieved, but similar alignment of graphene remains a challenge and has not been demonstrated, although theoretically study has been reported …”
mentioning
confidence: 99%
“…Graphene alignment using its diamagnetism was investigated theoretically, but a large field of 9 T was predicted, and experimental demonstration has not been reported. To detect the magnetic response of few‐layer graphene, we monitor the birefringence of its liquid suspension . This is a typical technique to probe the orientations of liquid crystal molecules as well as layered 2D nanomaterials.…”
mentioning
confidence: 99%
“…Recently, this technique has also been applied to investigate the field-induced alignment of CdSe nanorods [57] or the orientation of transition metal dichalcogenide nanodiscs. [58] Here, we use TEB to measure ground-state dipoles in colloidal CdSe nanoplatelets. We first recall the theoretical background necessary to understand the experiments that were conducted.…”
Section: Introductionmentioning
confidence: 99%